Penyuluhan Pemberdayaan Masyarakat Tentang Pencegahan dan Penanganan DBD Sekaligus Pemeriksaan Gratis - Dwi Ris Hasanah S; Suriati Lubis (Journal of Community Development, 2022)
Dengue fever (DHF) is a serious febrile illness transmitted by the bite of the female Aedes aegypti mosquito. The disease is of serious concern as it can be life-threatening if not treated promptly. DHF affects the human circulatory system and can result in serious complications or even death. Therefore, prevention and early treatment efforts are very important to reduce the impact of this disease. Health counseling activities on the prevention and treatment of DHF in hamlet IV of Lobu Huala village aim to increase community understanding of the importance of preventing and treating this disease. Through this activity, the community can gain the necessary knowledge to protect themselves and their families from the risk of DHF. The methods used in this counseling include providing information and education to the community on effective ways to prevent the spread of DHF. One of the main approaches is to eradicate the Aedes aegypti mosquito vector, which is the main cause of dengue transmission. The community is taught how to manage their surroundings, such as cleaning up stagnant water that can be a breeding ground for mosquitoes, and keeping their homes and yards clean. In addition, the counseling also provides information on the signs and symptoms of DHF, the first actions to take if someone is infected, and the importance of seeking immediate medical attention if symptoms worsen. With this knowledge, the community is expected to be more aware of the symptoms of DHF and take appropriate steps to prevent its spread. The results of this counseling activity showed that the community of hamlet IV of Lobu Huala village began to understand and implement better dengue mosquito eradication practices. They are also more aware of the importance of maintaining environmental hygiene and taking regular preventive measures. With this increased understanding, it is hoped that dengue cases in the area can be significantly reduced, so that the quality of life of the community can be improved and the risk of disease can be minimized.